Access to knowledge and education it the digital technologies era - Bogova, Hristina (ADA University Library, 2024)
The digital era is a new stage in the development of mankind, associated with the construction of a global information society based on data and knowledge. Nowadays, we can say with full confidence that humanity has entered a qualitatively new phase of its development related to the development of a global information digital society, the concept of which has become a common platform for interaction between all subjects of the modern economy in order to solve the problem of introducing a new production cycle, based on concepts such as information, data, knowledge and communication. At the same time, the global digital society is a society of continuous learning. In fact, the new cultural and historical context of human development in regard to the upcoming and actually developing, before our very eyes, fourth industrial revolution involves the transformation of production, economy and social sphere based on the widespread use of digital and hybrid technologies, focused on the use and processing of large amounts of data for decision-making and generation of new knowledge. The report examines the crisis experienced by the education system during the development of the digital economy. The main premise of this crisis is related to the following paradox: although the basis of the modern economy is the accumulation, processing and dissemination of knowledge, a fragmented perception of knowledge as such is developing in society. The purpose of the study is to highlight the most important characteristics of the educational crisis, as well as to determine its specifics in relation to the Bulgarian context.
Keywords: Digital economy; Authority of knowledge; Commercialization of higher education; Hybrid technologies